Virtue ethics reimagined: Aristotelian, Islamic, and Pancasila perspectives on character formation - Arief Rahman; Irma Yurni; Wachid Pratomo; Nurasih Shamadiyah; Eka Jayadiputra; Ella Dewi Latifah (LP2M Universitas Sarjanawiyata Tamansiswa, 2026)
This study integrates Aristotelian, Islamic, and Pancasila ethics to formulate an operational framework for fostering